Peranan Penerapan Sistem Akuntansi Accurate Terhadap Penyusunan Laporan Keuangan (Studi Kasus Pada Umkm Toko Textile Leuwi Di Bogor) - Mahardika, Agatha Gema; Pramiudi, Udi; Fahmi, Arief (Institut Bisnis dan Informatika Kesatuan, 2019)
The purposes of this study are (1) to identify the transaction recording system in micro, small, and medium scale enterprises, in this case the object of study, Textile Leuwi Shop, (2) to recognize the application of Accurate accounting system in Textile Leuwi Shop, and (3) to identify the role of Accurate accounting system application on the financial statements presentation in Textile Leuwi Shop. The research method used in this study is descriptive qualitative based on observation and data obtained. The author tried to explain how transactions were recorded, and the very same transaction data then applied into Accurate accounting system. There is also explanation on the impact of application of Accurate accounting system in Textile Leuwi Shop. The results showed that transactions are still recorded manually and that the shop has not yet make financial statement. Accurate then applied after previously carrying advanced preparation, entering and importing data. After all transaction processes were carried out, a financial report can be made available. The application of Accurate accounting system software guarantees a fast, easy and accurate report.